Halogen Bonding: A New Platform for Achieving Multi‐Stimuli‐Responsive Persistent Phosphorescence. Issue 13 (16th February 2022) - Dai, Wenbo; Niu, Xiaowei; Wu, Xinghui; Ren, Yue; Zhang, Yongfeng; Li, Gengchen; Su, Han; Lei, Yunxiang; Xiao, Jiawen; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; et al.
Abstract: Monotonous luminescence has always been a major factor limiting the application of organic room‐temperature phosphorescence (RTP) materials. Enhancing and regulating the intermolecular interactions between the host and guest is an effective strategy to achieve excellent phosphorescence performance. In this study, intermolecular halogen bonding (CN⋅⋅⋅Br) was introduced into the host–guest RTP system. The interaction promoted intersystem crossing and stabilized the triplet excitons, thus helping to achieve strong phosphorescence emission. In addition, the weak intermolecular interaction of halogen bonding is sensitive to external stimuli such as heat, mechanical force, and X‐rays. Therefore, the triplet excitons were easily quenched and colorimetric multi‐stimuli responsive behaviors were realized, which greatly enriched the luminescence functionality of the RTP materials. This method provides a new platform for the future design of responsive RTP materials based on weak intermolecular interactions between the host and guest molecules. Abstract : Intermolecular halogen bonding (CN⋅⋅⋅Br) was introduced into the host–guest room‐temperature phosphorescence (RTP) system, achieving fluorescence–phosphorescence dual‐emission. The weak intermolecular interactions of the halogen bond are sensitive to external stimuli (heat, mechanical force and X‐rays), realizing the colorimetric multi‐stimuli response behaviors.